ANALYZING THE CHEMISTRY MISCONCEPTIONS OF MIDDLE-SCHOOL STUDENTS RELATED TO ACIDS AND BASES USING A FOUR-TIER DIAGNOSTIC TEST - Nola Putri Erza, - (2023)
Students' conception has a crucial role in the learning process as it allows teachers to assess student comprehension and prevent misconceptions. One example science topic that students' have trouble in learning is chemistry such as acids and bases. Misconceptions occur when students hold alternative explanations or ideas that do not align with established scientific knowledge. The researchers focused on the topic of acids and bases properties are an important topic in middle school, yet there are many recurring misconceptions about it. To identify and address such misconceptions, the four-tier diagnostic test was developed as an improvement over the three-tier test. Instrument administered to 121 7th-grade students (51 male and 70 female). Data analysis was conducted using Excel to calculate percentages and frequencies. The findings revealed that, overall, students had more misconceptions (33.4%) than conceptions identified as scientific knowledge (19.9%), false positive (16.2%), false negative (15.9%), and lack of knowledge (14.7%). Their strongest performance was in understanding the characteristics of acids and bases, while they struggled the most with identifying acid and base solutions also determination scale acidity and alkalinity. The main causes of these misconceptions were identified as unconfronted misconceptions and unfamiliarity. As a result, the study highlights the importance for teachers to address common misconceptions in the classroom, by use the suitable teaching strategies for the students' conception.